Whole body-electromyostimulation effects on serum biomarkers, physical performances and fatigue in Parkinson’s patients: A randomized controlled trial - di Cagno, Alessandra; Buonsenso, Andrea; Centorbi, Marco; Manni, Luigi; Di Costanzo, Alfonso; Casazza, Giusy; Parisi, Attilio; Guerra, Germano; Calcagno, Giuseppe; Iuliano, Enzo; Soligo, Marzia; Fiorilli, Giovanni; et al. (Frontiers in Aging Neuroscience, 2023)
Background: Whole-body electromyostimulation (WB-EMS) was never previously applied to Parkinson's disease (PD) patients. This randomized controlled study aimed to find the most effective and safe WB-EMS training protocol for this population. Methods: Twenty-four subjects (age: 72.13 ± 6.20 years), were randomly assigned to three groups: a high-frequency WB-EMS strength training group (HFG) (rectangular stimulation at 85 Hz, 350 µs, 4 s stimulation/4 s rest), a low-frequency WB-EMS aerobic training group (LFG) (rectangular stimulation 7 Hz, 350 µs, with a continuous pulse duration), and an inactive control group (CG). Participants of the two experimental groups underwent 24 controlled WB-EMS training sessions, with a duration of 20 min each, during 12-week intervention. Serum growth factors (BDNF, FGF-21, NGF and proNGF), α-synuclein, physical performance and Parkinson's Disease Fatigue Scale (PFS-16) responses were analysed to evaluate the pre-post variation and differences among groups. Results: Significant interactions of Time*Groups were detected for BDNF (Time*Groups p=0.024; Time*CG, b=-628, IC95%=-1082/-174, p=0.008), FGF-21 (Time*Groups p=0.009; Time*LFG b=1346, IC95%=423/2268, p=0.005) and α-synuclein (Time*Groups p=0.019; Time*LFG b=-1572, IC95%=-2952/-192, p=0.026). Post hoc analyses and comparisons of ΔS (post–pre), performed independently for each group, showed that LFG increased serum BDNF levels (+203 pg/ml) and decreased α-synuclein levels (-1703 pg/ml), while HFG showed the opposite effects (BDNF: -500 pg/ml; α-synuclein: +1413 pg/ml). CG showed a significant BDNF reduction over time. Both LFG and HFG showed significant improvements in several physical performance outcomes and the LFG showed better results than HFG. Concerning PFS-16, significant differences over time (b=-0.4, IC95%=-0.8/-0.0, p=0.046) and among groups (among all groups p<0.001) were found, and the LFG exhibited better results than the HFG (b=-1.0, IC95%=-1.3/-0.7, p<0.001), and CG (b=-1.7, IC95%=-2.0/-1.4, p<0.001) with this last one that worsened over time. Conclusion: LFG training was the best choice for improving or maintaining physical performance, fatigue perception and variation in serum biomarkers.